Modulation of the c-JNK/p38-MAPK signaling pathway: Investigating the therapeutic potential of natural products in hypertension - Rakesh Sahu; Ravindra K. Rawal (Elsevier, 2024)
Background: Cardiovascular problems, particularly hypertension, are the leading causes of mortality and disability. The pathogenesis of high blood pressure involves the dysregulation of cellular and metabolic processes, including the c-Jun-N-terminal Kinase (c-JNK) and p38-mitogen-activated protein kinase (p38-MAPK) pathways. The impairment of the c-JNK/p38-MAPK pathway causes normal and unusual immunological responses, such as the stimulation of leukocyte adhesive molecules, the secretion of inflammatory mediators, and the synthesis of chemokines. Natural compounds have been excellent sources of novel therapeutic drugs and contributed to the research and investigation of alternative antihypertensive medications. Methods: This review investigates how natural products affect the cardioprotective potentials by regulating the c-JNK/p38-MAPK pathway. The literature on natural compounds having cardioprotective potentials was found by searching scientific databases, including SciFinder, Medline, Google Scholar, and ScienceDirect. Results: Natural products have a significant therapeutic efficacy in the treatment of hypertension and other cardiovascular complications, such as angina, myocardial ischemia, and cardiovascular disease. Natural compounds have an impact on several facets of the pathway, affecting cellular activities linked to hypertension, inflammation, and immunological responses. Conclusions: The review focuses on the potential therapeutic use of natural products targeting the c-JNK/p38-MAPK signaling pathway in the treatment of hypertension. Their potential for developing antihypertensive drugs in the future is attractive due to their cardioprotective qualities, which might lead to better treatment results for cardiovascular diseases.